Large Scale Integration of Functional Radio‐Frequency Flexible MEMS under Large Mechanical Strain. (28th November 2022) - Azrak, Edy; Michaud, Laurent; Richy, Jérôme; Reinhardt, Alexandre; Tardif, Samuel; Eymery, Joël; Bousquet, Marie; Fournel, Frank; Montmeat, Pierre
Abstract: A versatile industrial recipe of transferring nitride microelectronic components such as micro‐electromechanical systems (MEMS) onto flexible and stretchable substrates is demonstrated. This method bypasses difficulties of temperature‐related processing, and is applicable to large‐scale and mass production. The technological process of fabrication is presented along with its underlying structural and radio‐frequency characterizations. In particular, the Raman strain shifts of aluminum nitride (AlN) thin films are determined for uniaxial and biaxial mechanical deformations. The transferring process onto polymer is also demonstrated by an adhesive bonding of AlN‐based MEMS onto a 200 mm silicon (Si) wafer. The devices microstructure is assessed using X‐ray before and after transferring, as well as their electrical radio‐frequency (RF) features when on Si and polymer substrates. Then, RF measurements are also performed on the transferred and flexible devices; some in their relaxed states, and others in an in situ manner under an increasing macroscopic strain. It is shown that bulk acoustic wave resonator MEMS are fully functional even under 12% uniaxial stretching of the substrate. Abstract : A process of transferring nitride microelectronic components such as MEMS (micro‐electromechanical systems) from a silicon substrate onto flexible and stretchable substrates is demonstrated.The fabrication is presented along with its underlying structural and characterizations. Radio‐Frequency measurements are performed on the transferred and flexible devices. Bulk acoustic wave resonator MEMS are fully functional even under 12% uniaxial stretching.